Describing the clinical reasoning process: Application of a model of enablement to a pediatric case. (April 2013) - Furze, Jennifer; Nelson, Kelly; O'Hare, Megan; Ortner, Amanda; Threlkeld, A. Joseph; Jensen, Gail M.
<x xml:space="preserve">Abstract</x> Background and purpose: Clinical reasoning is a core tenet of physical therapy practice leading to optimal patient care. The purpose of this case was to describe the outcomes, subjective experience, and reflective clinical reasoning process for a child with cerebral palsy using the International Classification of Functioning, Disability, and Health (ICF) model. Case description: Application of the ICF framework to a 9-year-old boy with spastic triplegic cerebral palsy was utilized to capture the interwoven factors present in this case. Interventions in the pool occurred twice weekly for 1 h over a 10-week period. Outcomes: Immediately post and 4 months post-intervention, the child made functional and meaningful gains. The family unit also developed an enjoyment of exercising together. Each individual family member described psychological, emotional, or physical health improvements. Discussion: Reflection using the ICF model as a framework to discuss clinical reasoning can highlight important factors contributing to effective patient management.